X-Ray Crystallographic Studies of (?-4-(Iodophenoxy)- ?-(1,1-dimethylethyl)-1H-1,2,4-triazole-1-ethanol) - Sengar, Jyotsna (Asian Journal of Chemistry, 2010)
Recently, it has been observed that some of these fungicides are lossing their effects and becoming resistant to them. Analogous compounds can be designed as substitute, if their structures are known. A rational approach to test these fungicides is to know the three dimensional structure of these compounds and macromolecular receptor sites as well as their molecular complex. In present studies, crystal and molecular structure of systemic fungicide (β-4-(iodophenoxy)-α-(1,1-dimethylethyl)-1H-1,2,4-triazole- 1-ethanol) is carried out. The unit cell parameters were determined by directly on CAD-4 Enraf Nonius 4-circle automatic diffractometer in ω-2θ scan mode using Ni-filtered CuKα λ (1.5418 Å) radiations. The unit cell parameters are a = 8.136(2) Å, b = 16.762(1) Å, c = 21.979(1) Å, α = 90(1)º, β = 92.54(2)º, γ = 90(2)º. The space group was determined to be P21/n.